(untitled) - Cotton, David (England, 2005)
Learn from stimulating authentic materials such as the world-renowned Financial Times *Enhance language and business skills through case study tasks. Based on realistic business scenarios, these tasks give students an opportunity to practice *Tailor your lessons to the individual needs of your students with the wide range of components and specialist titles available.
Keywords: English language; Study and teaching